Stainless steel in architecture, building and construction : guidelines for roofs, floors and handrails. (Nickel Development Institute, 1994)
This publication describes correct type of stainless steel associated with architectural and building products i.e. roofs, floors and handrails.
Keywords: Stainless steel.; elektronické knihy; electronic books